Some Royal Provincial Belt Plates and the Revolutionary War:: Vanguard of British Neo-classicism in America? - Hughes, Gary (Material Culture Review)

(untitled) (National Museums of Canada, 2011)
Abstract The arrival of British Neo-classicism in the newly minted American republic is usually seen as an opening phase in the advancement of national expression. Independence coincided with Robert Adam’s influence on the Federal style, followed by Thomas Jefferson’s idealism, the rationalism of Benjamin Latrobe and, finally, the Greek Revival. The preceding war years are usually treated as a period of arrested development but during the conflict there is evidence that Loyalist Americans were aware of Adam’s revolution in style, especially in New York City. This study examines the reaction to this influence through the work of silversmith Lewis Fueter who produced shoulder belt plates for Royal Provincial or Loyalist troops during the war. His designs and attributions reflect an earlier and different iconographic connection to Adam couched not in terms of national identity but rather that of the wider Anglo-American community.